Literature Study On Media Impact Social To Adolescent Mental Health - Putra Apandi; Taty Djuwita; Laura Aminah (Nusantara: Journal of Cultural Research, 2025)
Technology is currently developing very rapidly, especially the internet, which isreferred to as a social network. It seems to eliminate distance, space, and time, allowing peopleto connect with anyone, anytime. Social media brings many impacts, both positive andnegative. The majority of social media users are teenagers and children who still requiresupervision, and therefore the greatest impact is directed toward them. Social media haspositive effects and benefits for the development of science and technology, such as makingcommunication easier, helping to search for and access information, expanding relationships,making new friends, and so on. However, on the other hand, social media also has negativeimpacts on children and society. Teenagers show behavioral changes after becoming addictedto social media, such as becoming lazy due to being too absorbed in it. With social media, theyalso tend to neglect their responsibilities as students.